2013
DOI: 10.1161/circinterventions.112.000076
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Comparison of Sirolimus-Eluting and Everolimus-Eluting Coronary Stents in the Treatment of Total Coronary Occlusions

Abstract: Second-generation DESs have provided better platforms, new drugs, and new polymers, with the objective of improve deliverability and even safety of these devices. Among them, Background-Patients with coronary total occlusions are at especially high risk for restenosis and new revascularizations.Sirolimus-eluting stents dramatically improved the clinical outcome of this subset of patients in randomized trials, but other drug-eluting stents, mainly the everolimus-eluting stent (currently the most frequently used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 25 publications
3
23
1
3
Order By: Relevance
“…Third, the effect of EES relative to SES could be more pronounced in complex coronary artery disease. 26,27 However, because of the lack of patient-level data, the present analysis could not address the effect in patients with complex coronary artery disease, such as chronic total occlusion, bifurcation, hemodialysis, and long lesion. Finally, SES has already disappeared from the commercial market.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the effect of EES relative to SES could be more pronounced in complex coronary artery disease. 26,27 However, because of the lack of patient-level data, the present analysis could not address the effect in patients with complex coronary artery disease, such as chronic total occlusion, bifurcation, hemodialysis, and long lesion. Finally, SES has already disappeared from the commercial market.…”
Section: Discussionmentioning
confidence: 99%
“…The total stent length was 43.4 AE 21.5 mm for ZES compared with 44.6 AE 20.2 mm for SES, again clearly lower compared with our population. In the CIBELS trial (Randomized Comparison of Sirolimus-Eluting and EverolimusEluting Coronary Stents in the Treatment of Total Coronary Occlusions) patients with TIMI 0 or I and an estimated occlusion time of more than 2 weeks were enrolled [21]. Total stent length was 47.5 AE 24.6 mm [21].…”
Section: Discussionmentioning
confidence: 99%
“…In the CIBELS trial (Randomized Comparison of Sirolimus-Eluting and EverolimusEluting Coronary Stents in the Treatment of Total Coronary Occlusions) patients with TIMI 0 or I and an estimated occlusion time of more than 2 weeks were enrolled [21]. Total stent length was 47.5 AE 24.6 mm [21]. In the PEPCAD-CTO registry we compared the paclitaxelcoated balloon (PCB) plus bare-metal stent for true CTOs with a TIMI 0 flow and duration of occlusion of more than 3 months with the paclitaxel eluting stent (PES) [22].…”
Section: Discussionmentioning
confidence: 99%
“…Long-term outcomes after CTO-PCI are favorable, with most studies demonstrating low rates of restenosis and target lesion revascularization (,10% at 1 year), [43][44][45][46][47][48][49][50][51] although some studies with highly complex lesions have reported higher restenosis rates. 52 First-generation drugeluting stents (DES) significantly reduced the risk of restenosis compared with bare metal stents.…”
Section: N Long-term Outcomes After Cto-pcimentioning
confidence: 99%